Design A Battery Charger with Arduino Uno-Based for A Wind Energy Power Plant - Anggara Trisna Nugraha; Dadang Priyambodo; Sryang Tera Sarena (Universitas Negeri Malang, 2022)
In 2019, fossil energy produced more than 88% of Indonesia's electrical energy. For this reason, innovation in supplying electrical energy via renewable energy is required. One of them is wind energy with a potential of 60.6 GW, which has only been utilized at 0.15 GW or only 0.25% of the existing potential. One of the essential components in this power plant is the battery. The process of charging the battery that is not suitable can cause a decrease in battery performance. Therefore, a battery charger is built that uses a buck converter to lower the voltage while employing PI control to regulate the output voltage. From system testing, it is found that the output voltage of the charge controller is stable, where the most significant error value from the output voltage value is 0.972%. The average output current from the buck converter test using the PI approach is 16.84 mA, while the average input current is 15.73 mA. As a result, this charge controller can improve the battery charger's charging efficiency and hence lengthen the battery's lifetime.DOI: 10.17977/um024v7i12022p023